Hannah Hippo's New Helper My Storytime - Ronne Randall (Italy Ladybird Books, 2009)
All the hippos down by the muddy river have a special bird friend to eat the itchy insects that land on them. All except Hannah Hippo! Hannah needs to go on a journey through the jungle to find herself a helper. This is an ideal first storybook with bright, bold illustrations. It is perfect for bedtime and storytime.